Cediranib phase‐II study in children with metastatic alveolar soft‐part sarcoma (ASPS). Issue 12 (10th September 2019) - Cohen, Julia W.; Widemann, Brigitte C.; Derdak, Joanne; Dombi, Eva; Goodwin, Anne; Dompierre, Jessica; Onukwubiri, Uzoma; Steinberg, Seth M.; O'Sullivan Coyne, Geraldine; Kummar, Shivaani; Chen, Alice P.; Glod, John
Abstract: Background: Alveolar soft‐part sarcoma (ASPS), a rare vascular sarcoma with a clinically indolent course, frequently presents with metastases. Vascular endothelial growth factor (VEGF) is a promising therapeutic target. In a phase‐II trial of the VEGF receptor inhibitor cediranib for adults with ASPS, the partial response (PR) rate (response evaluation criteria in solid tumors [RECIST] v1.0) was 35% (15/43; 95% confidence interval: 21‐51%). We evaluated cediranib in the pediatric population. Procedure: Patients <16 years old with metastatic, unresectable ASPS received cediranib at the pediatric maximum tolerated dose of 12 mg/m 2 (≈70% of the fixed adult phase‐II dose orally daily). Tumor response was assessed every two cycles (RECIST v1.0). A Simon two‐stage optimal design (target response rate 35%, rule out 5%) was used. Results: Seven patients (four females), with a median age of 13 years, (range 9‐15), were enrolled on stage 1. The most frequent grade 2 or 3 adverse events were neutropenia, diarrhea, hypertension, fatigue, and proteinuria. The best response was stable disease (SD) (median cycle number = 34). Three patients were removed from the study treatment for disease progression (cycles 4, 5, and 36). Five of seven patients had SD for ≥14 months. Two patients with SD remain on study (34‐57+ cycles). Conclusions: Cediranib did not reach the target response rate in this small pediatric cohort, in contrast to the adult 35% PR rate. The pediatric dosing was 30% lower compared to the adult dosing, which may have contributed to response differences. Prolonged SD was observed in five patients, but given the indolent nature of ASPS, SD cannot be clearly attributed to cediranib. Cediranib has an acceptable safety profile.